2003
DOI: 10.1001/archneur.60.8.1059
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-inflammatory Drugs and the Risk of Parkinson Disease

Abstract: These findings are consistent with the hypothesis that use of NSAIDs may delay or prevent the onset of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
342
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(359 citation statements)
references
References 33 publications
(17 reference statements)
15
342
1
1
Order By: Relevance
“…These inflammatory molecules, along with factors released from the dying dopaminergic cells, seem to amplify and sustain neuroinflammation as well as neural cell toxicity leading to a slow and irreversible destruction of SN dopaminergic neurons. In agreement with McGeer's hypothesis on the role of activated glial cells and brain inflammation in PD, administration of nonsteroidal anti-inflammatory drugs were shown to reduce the risk of PD ( [38,207,245]), suggesting that inhibitors of inflammation are promising therapeutics for PD.…”
Section: Parkinson's Disease and Neuroinflammationsupporting
confidence: 72%
“…These inflammatory molecules, along with factors released from the dying dopaminergic cells, seem to amplify and sustain neuroinflammation as well as neural cell toxicity leading to a slow and irreversible destruction of SN dopaminergic neurons. In agreement with McGeer's hypothesis on the role of activated glial cells and brain inflammation in PD, administration of nonsteroidal anti-inflammatory drugs were shown to reduce the risk of PD ( [38,207,245]), suggesting that inhibitors of inflammation are promising therapeutics for PD.…”
Section: Parkinson's Disease and Neuroinflammationsupporting
confidence: 72%
“…For aspirin and acetaminophen, no associations were observed. There was no dose-response relationship, however, between non-aspirin NSAIDs and PD [557]. When the same authors followed up their finding in the Cancer Prevention Study II Nutrition cohort, with more detailed information on type of NSAIDs, they found lower PD risk associated with ibuprofen (p for trend 0.03), but not with other NSAIDs, aspirin or acetaminophen [558].…”
Section: Inflammationmentioning
confidence: 97%
“…The prospective Nurses Health Study and the Health Professionals Follow-up Study initially reported lower risk of PD associated with regular use of non-aspirin NSAIDs (pooled RR 0.55, 95% CI 0.32-0.96) [557]. For aspirin and acetaminophen, no associations were observed.…”
Section: Inflammationmentioning
confidence: 98%
“…It has been reported that inflammation is up-regulated in brains of PD patients (McGeer et al, 1988;Whitton, 2007), and parallel changes in microglial activation and corresponding dopaminergic terminal loss are observed in the affected nigrostriatal pathway of early PD (Ouchi et al, 2005). Despite some controversial findings, the beneficial effects of non-aspirin and nonsteroidal antiinflammatory drugs (NSAIDs) on PD progression have been supported by several epidemiological studies (Chen et al, 2003;Hernan et al, 2006;Ton et al, 2006), suggesting that antiinflammatory agents may prevent neuronal death in PD. In an experimental PD model, NSAIDs, aspirin, meloxicam, indomethacin and rofecoxib, have displayed neuroprotective effects in vivo (Kurkowska-Jastrzebska et al, 2002;Teismann and Ferger, 2001;Teismann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%